2016
DOI: 10.6001/actamedica.v23i2.3327
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of advanced stage yolk sac tumour of extragonadal origin: a case report and review of literature

Abstract: Background.Yolk sac tumour diagnosis should be considered for young age patients admitted to the hospital with non-specific complaints of widespread disease. Correct diagnosis and carefully planned treatment is the key to a successful outcome.Methods and materials. We present a rare case of a widespread yolk sack tumour of a uterine broad ligament. Our team directed a special attention towards the patient’s young age, advanced disease, and fertility sparing strategy of treatment.Results and conclusions.Stage I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…On MRI, yolk sac tumors can show areas of signal voids related to rich vascularization [ 15 ] or areas of hemorrhage. Cross-sectional imaging is valuable in the assessment of the full extent of metastatic spread into the lymph nodes, omentum, lungs, liver, and bones [ 16 ]. In advanced stages, surgical treatment aims to provide complete cytoreduction without systematic lymph node dissection; however, the procedure may be modified to minimize surgical morbidity in view of high chemosensitivity to ensure no delays in postoperative chemotherapy [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…On MRI, yolk sac tumors can show areas of signal voids related to rich vascularization [ 15 ] or areas of hemorrhage. Cross-sectional imaging is valuable in the assessment of the full extent of metastatic spread into the lymph nodes, omentum, lungs, liver, and bones [ 16 ]. In advanced stages, surgical treatment aims to provide complete cytoreduction without systematic lymph node dissection; however, the procedure may be modified to minimize surgical morbidity in view of high chemosensitivity to ensure no delays in postoperative chemotherapy [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a case reported by Rudaitis et al 27 , NACT with four PEB cycles was chosen as an option to reduce tumor size and minimize the extent of the surgical procedure. In our case, the preoperative histology of the YST was acquired by biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that platinum-based chemotherapy should be used for the more malignant tumors such as endodermal sinus tumor and mixed germ cell tumor (45, 46). Neoadjuvant chemotherapy could be considered for the patients having extensive intra-abdominal disorders when initial surgical debulking is not preferred (47). Chemotherapy is suggested for treating recurrence (37).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, minimally invasive surgery has been proved to have better prognosis (34). Rudaitis et al (47) applied neoadjuvant chemotherapy of four BEP cycles to decrease the tumor size in order to minimize the extent of surgery and thus the impact on the patient's fertility. In spite of the risks of damaging the reproductive function of female patients involved in chemotherapy, previous investigations have revealed that most of the women could recover their normal menstrual and reproductive functions post treatment (49, 50).…”
Section: Discussionmentioning
confidence: 99%